2018
DOI: 10.3329/jsr.v10i1.33858
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Antifungal Evaluation of Chloroflavones

Abstract: Two chloroflavones, 6 and 7 along with their corresponding chalcones, 4 and 5 have been tested for antibacterial and antifungal activities against six human pathogenic bacteria viz. Bacillus cereus (G+), Staphylococcus aureus (G+), Escherichia coli (G-), Vibrio choloriae (G-), Pseudomonas aeruginosa (G-), and Salmonella typhi (G-), and four plant as well as mold fungi viz. Aspergillus flavus, Aspergillus ochraceus, Aspergillus niger and Rhizopus spp.. The antibacterial and antifungal screens of the synthesized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Four Gram-positive and five Gram-negative human pathogenic bacteria, and four human fungal pathogens were collected from the Biochemistry Laboratory, Department of Biochemistry and Molecular Biology, University of Chittagong, Bangladesh (Table 1). Antibacterial activities were screened in vitro disc diffusion method [29][30][31] and antifungal efficacy was evaluated in vitro food poisoning technique [32][33][34][35]. Proper control was maintained with DMF (dimethylformamide) without chemicals.…”
Section: Evaluation Of In Vitro Antimicrobial Activitiesmentioning
confidence: 99%
“…Four Gram-positive and five Gram-negative human pathogenic bacteria, and four human fungal pathogens were collected from the Biochemistry Laboratory, Department of Biochemistry and Molecular Biology, University of Chittagong, Bangladesh (Table 1). Antibacterial activities were screened in vitro disc diffusion method [29][30][31] and antifungal efficacy was evaluated in vitro food poisoning technique [32][33][34][35]. Proper control was maintained with DMF (dimethylformamide) without chemicals.…”
Section: Evaluation Of In Vitro Antimicrobial Activitiesmentioning
confidence: 99%
“…Substances with new properties obtained using environmentally friendly methods are constantly sought after in the pharmaceutical, cosmetic, and food industries [27,28]. It is known that flavonoid compounds have valuable properties: antioxidant [29,30], anticarcinogenic [30,31], modulating intestinal immune responses [32], hepatoprotective [32,33], antimicrobial [34][35][36], and others.…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria that are resistant to antibiotics are a significant global problem nowadays. Flavonoid compounds with bromine and chlorine atoms and methyl and nitro groups may be the solution, as some of them show bacteriostatic/bactericidal properties [36,37]. The antibiotic potentiating activity test demonstrated that the (2E)-1-(3 -methoxy-4 -hydroxyphenyl)-3-(3nitrophenyl)prop-2-en-1-one chalcone (called AVMNB) associated with the antibiotics has activity against multi-resistant strains of bacteria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to biological importance, in addition to isolation from natural sources, several strategies for the synthesis of chalcones and flavones have so far been reported [1,7]. In a similar context, we have also reported the synthesis and antimicrobial effects of several heterocycles and flavonoids containing various groups in their ring system [10][11][12][13][14]. Among the synthetic strategies, Claisen-Schmidt condensation [7], oxidative cyclization of 2hydroxychalcones [15,16], three-step Baker-Venkataraman rearrangement [7], and the cyclodehydration of 1-(2-hydroxyphenyl-3-phenyl-1,3-propanedione) [17] were commonly used.…”
Section: Introductionmentioning
confidence: 99%